"Rationally Local": Consumer Participation in Alternative Food Chains. Issue 3 (9th April 2015) - Cembalo, Luigi; Lombardi, Alessia; Pascucci, Stefano; Dentoni, Domenico; Migliore, Giuseppina; Verneau, Fabio; Schifani, Giorgio
ABSTRACT Why are consumers increasingly participating in alternative food chains to co‐produce and distribute foods with farmers? In this paper, values and food‐related lifestyles, as well as transaction costs and socio‐demographics, are used to analyze consumer participation in alternative food chains in Italy. Using a simultaneous system of equations, a model with instrumental variables is implemented to measure the relationships between values and food‐related lifestyles, and between the latter and participation in an alternative food chain. Our results show that Italian participants in alternative food chains have the profile of rational shoppers who typically look at price and taste criteria. Although transaction costs do not affect participation directly, they do so through food‐related lifestyles.